The effects of foot orthoses and sensory facilitation on lower limb electromyography: A scoping review. (September 2022) - Robb, Kelly A.; Howe, Erika E.; Perry, Stephen D.
Highlights: Foot orthoses likely modify stimuli from foot sole cutaneous afferents. Sensory input modulates the excitability of motorneuron pools. Skin should be considered in foot orthoses designs to modulate electromyography. Abstract: Foot orthoses (FO) are used as a treatment for biomechanical abnormalities, overuse injuries, and neuropathologies, but study of their mechanism remains inconclusive. The neuromotor paradigm has proposed that FOs may manipulate sensory input from foot sole skin to reduce muscle activity for movement optimization. This review argues that a FO likely alters the incoming mechanical stimuli transmitted via cutaneous mechanoreceptors and nociceptors as the foot sole interfaces with the surface of the orthotic. Thus, all FOs with or without intentional sensory facilitation, likely changes sensory information from foot sole cutaneous afferents. Additionally, in light of understanding and applying knowledge pertaining to the cutaneous reflex loop circuitry, FO's increasing sensory input to the motorneuron pool can change EMG to either reflex sign (increase or decrease). The purpose of this scoping review was to synthesize FO and sensory augmentation literature and summarize how FO designs can capitalize on foot sole skin to modulate lower limb electromyography (EMG). Six database searches resulted in 30 FO studies and 22 sensory studies that included EMG as an outcome measure. Results revealed task and phase specific responses with some consistencies in EMG outcomes between testing modalities, however many inconsistencies remain. Electrical stimulation reflex research provides support for a likely sensory-to-motor factor contributing to muscle activity modulation when wearing FOs. The discussion divides trends in FO treatment modalities by desired increase or decrease in each compartment musculature. The results of this review provides a benchmark for future academics and clinicians to advance literature in support of a revised neuromotor paradigm while highlighting the importance of foot sole skin in FO design.